The Role and Impact of Dowry in the delay of Matrimony (Nikah)in Pashtun Society: An Analytical Study - Dr. Zia Ur Rehman; Dr. Atta Ur Rahman; Dr. Rab Nawaz (International Research Journal of Arabic and Islamic Studies, 2023)
Nikah (connubiality) is the only undisciplined way of physical commerce between a man and woman. It plays an important part to satisfy the spontaneous requirements of man and woman and also insure gravidity. Dower( Mahar) is one of the introductory conditions of Nikah. It's a token plutocrat that manifests quality of woman and shows the commitment of the husabnd that the responsibility of earning rests on his shoulders. The end of this study is to punctuate the traditions regarding Mahar in contemporary Pashtun society in District Charsadda, Khyber Pakhtunkhwa. Data was collected through questionnaire from wedded people, both manly and womanish, to know about the customs and traditions of contemporary Pashtun Society regardinging Mahar. Analysis was done by using descriptive statistics i- e data table. The study shows that utmost of the people are apprehensive of the Islamic principles regarding Mahar as an obligation but still there's inconsistenct between oral conviction and deed with trference to the payment of Mahar. Dower is considered as a mark of respect for women in Islam. There's the tradition of giving gold as dower that's paid at the time or after the connubiality.